2018
DOI: 10.1021/acsami.7b18525
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Delivering High-Density Lipoprotein-like Nanoparticles as a Biomimetic Nanotherapy for Vascular Diseases

Abstract: Disorders of blood vessels cause a range of severe health problems. As a powerful vasodilator and cellular second messenger, nitric oxide (NO) is known to have beneficial vascular functions. However, NO typically has a short half-life and is not specifically targeted. On the other hand, high-density lipoproteins (HDLs) are targeted natural nanoparticles (NPs) that transport cholesterol in the systemic circulation and whose protective effects in vascular homeostasis overlap with those of NO. Evolving the AuNP-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 70 publications
(166 reference statements)
1
36
0
Order By: Relevance
“…In this study, and in many previous studies using the HDL NP as systemic therapy in animal models, we have noted a lack of toxic side effects (21,24,25,37,43,44). We also reported that HDL NP treatment of primary human hepatocytes and macrophages, the two most abundant normal cell types that express SCARB1, did not result in toxicity and that each of the normal cell types tightly regulated cholesterol homeostasis when treated with the HDL NP or native human HDL (24).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, and in many previous studies using the HDL NP as systemic therapy in animal models, we have noted a lack of toxic side effects (21,24,25,37,43,44). We also reported that HDL NP treatment of primary human hepatocytes and macrophages, the two most abundant normal cell types that express SCARB1, did not result in toxicity and that each of the normal cell types tightly regulated cholesterol homeostasis when treated with the HDL NP or native human HDL (24).…”
Section: Discussionsupporting
confidence: 70%
“…Here, we verified the requirement of SCARB1 as a target of HDL NP in these lymphoma cells using an anti-SCARB1 blocking antibody and fluorescently labeled HDL NPs. HDL NPs were fluorescently labeled using the intercalating dye DiI, as previously described (21,37). Ramos and SUDHL4 cells were treated with DiI HDL NPs for 2 hours followed by flow cytometric analysis.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, reduction of miR-92a levels has been shown to reduce infarct size and post-ischemic loos of cardiac function by displaying cell-protective, pro-angiogenic, and anti-inflammatory effects, whereas miR-486 has demonstrated to prevent cardiomyocyte apoptosis execution [60][61][62][63]. These promising experimental data have encouraged the development of synthetic HDL-like formulations containing, within the structural HDL components, locked nucleic acid-modified antisense against a given miRNA or different proportion of these candidate miRNAs [64].…”
Section: Protection Against Ischemia/reperfusionmentioning
confidence: 99%
“…Lastly, the in vivo study demonstrated that the mice only developed 27.83% of atherosclerotic plaque after treated with SNO HDL-NPs, which was much less than that of the PBS-treated mice (48.13 ± 4.82%) ( Fig. 3e-i) [55].…”
Section: Hdl Mimicking Nps As Therapeutic Delivery Systemsmentioning
confidence: 88%